NOTE SUR LES GENRES PALEOTROPICAUX AFZELIA, INTSIA ET PAHUDIA (Legum.-Caesalp.) - J. J. G. LEONARD (Reinwardtia, 1950)
1. Afzelia,Intsia,Pahudia,and Afrafzelia are very close to each other andnot well defined genera. 2. Intsia is a good genus, but the three,other ones are congeneric with eachother. 3. Afzelia Smith is a nomen conservandum and,therefore, must be maintained against Pahudia, generally used in Asiatic and Malaysian floras. 4. An enumeration of all species of Afzelia is given.In this connection some new combinations are made